Co-workers' impact on attitudinal behavior of the faculty members of educational institutions of Nepal - Gaire, Amrit Kumar Sharma; KC, Fatta Bahadur (Journal of Advanced Academic Research, 2017)
This paper attempts to analyze the relationship between co-workers' behavior and its impact on attitudinal behavior of the faculty members. The co-worker's behavior such as team support and lack of team support are used as an independent dimension and employee attitudinal behavior such as job satisfaction, job performance and job commitment are used as a dependent variable. The major objective of this research was to identify the effect on attitudinal behavior of faculty members' of higher educational institutions of Nepal due to their co-worker's behavior. Pair t- test was used to examine between the current and expectation co-worker's behavior of faculty members in the working place. Similarly, the one way analysis of variance was also used to test the hypothesis. The sample size was 400 faculty members. The findings show that here is significant relationship between the current and expected perception of the faculty towards the co-workers’ behavior. Similarly, the findings of team support co-workers’ behavior has positive significant and with lack of team support co-workers’ behavior has negatively significant difference with attitudinal behavior of the faculty.